COVID-19: AN APPLIED INTERVENTION THROUGH AYURVEDA (International Journal of Ayurveda and Pharma Research, 2020)
The world is crippling due to pandemic coronavirus disease (COVID-19) which is caused by severe acute respiratory syndrome Coronavirus (SARS-CoV-2). This situation can be considered under Janapadodhwamsa (destructions of states or kingdoms or countries) as mentioned in Ayurveda. Further, COVID-19 infection may be correlated with Vata-Kaphaja Sannipataja Jwara (a type of fever mentioned in classical Ayurvedic texts with severe complications and fatality). The article is mainly intended to interpret direct correlation between pandemics and Janapadodhwamsa, understanding the concept of COVID-19 and its probable management principles based on ethics of Ayurveda. The main aim of management principles includes correction of the Vikruta (contaminated) Vayu (air) and Desha (place/continent etc.) and improving the strength and immunity for prevention of disease as well as the management of COVID 19 patients by various herbal or herbo-mineral combinations based on the stage/severity of the disease along with follow up of recovered patients to avoid the recurrence.Considering above comprehensive aspect in management of COVID-19, the role of Ayurveda intervention may be proved more beneficial in asymptomatic, mild and moderate stages. Further, clinical studies on these drugs need to be conducted to produce evidence for safety and efficacy on COVID-19 for wider acceptance and implementation of Ahara Vidhis, Dinacharya and Sadvritta in National Health Policies for improving disease resistance.